‘Nulla’ (‘noughtes’) e ‘annullamenti’ (‘noughtinges’) nel testo breve di Giuliana di Norwich: un’analisi letteraria - Zaccara, Angela (De Medio Aevo, 2022)
Which is the structure of Julian of Norwich’s short text? This issue has hardly ever been explored. Notwithstanding, it is important to the understanding of the work’s meaning. My essay is a literary analysis aimed at showing that Julian turned her revelations into a spiritual programme divided, according to tradition, into steps. Its reference points are the “thre noughtes” that Julian mentions in her first vision, as there is evidence that they are the focus of a prologue, they mark the stages of an ascent to God, they are at the heart of a tripartite conclusion. This structure reflects the three wounds (of contrition, compassion, longing for God) that Julian had desired to receive from God when she was young and offers a reading of the short text independently of the long text. My analysis tries to answer another rarely explored question: what are exactly the “thre nougthes” to which Julian refers in her first vision? My identification is based on a strictly linguistic issue, which has never been taken into account: the morphological and semantic difference between ‘nought’ (noun) and ‘noughten’ / ‘noughtinge’ (verb and gerund respectively).